Knowledge and the flow of information - Dretske, Fred I. (CSLI Publications, 1999)
This book presents an attempt to develop a theory of knowledge and a philosophy of mind using ideas derived from the mathematical theory of communication developed by Claude Shannon. Information is seen as an objective commodity defined by the dependency relations between distinct events. Knowledge is then analyzed as information caused belief. Perception is the delivery of information in analog form (experience) for conceptual utilization by cognitive mechanisms. The final chapters attempt to develop a theory of meaning (or belief content) by viewing meaning as a certain kind of information-carrying role.